Programmed Death-Ligand 1 Expression and Its Correlation with Lymph Node Metastasis in Papillary Thyroid Carcinoma - Hyo Jung An; Gyung Hyuck Ko; Jeong-Hee Lee; Jong Sil Lee; Dong Chul Kim; Jung Wook Yang; Min Hye Kim; Jin Pyeong Kim; Eun Jung Jung; Dae Hyun Song (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Background The immunotherapeutic role of programmed death-ligand 1 (PD-L1) in life expectancy in many cancers has been highlighted. However, data regarding PD-L1 expression in papillary thyroid carcinoma (PTC) are limited. In this study, we describe the PD-L1 and programmed cell death protein 1 (PD-1) expressions in PTC and analyze their correlation with lymph node (LN) metastasis. Methods Clinicopathological data were obtained from 116 patients with PTC who were treated in Gyeongsang National University Hospital, Jinju, Korea in 2009. Tissue microarray blocks were made using representative paraffin blocks of classical PTCs excluding follicular variants. Two pathologists graded the proportion and intensity of PD-L1 and PD-1 expression in both tumor and inflammatory cells. According to their proportions, positive PTC cells were scored as negative (0%), grade 1 (1%-50%), and grade 2 (51%-100%). Similarly, positive inflammatory cells were graded as negative (0%), grade 1 (1%-10%), and grade 2 (11%-20%). The intensity of each protein expression was simplified as positive or negative. Results A statistically significant correlation exists between the proportions of PD-1 and PD-L1 expression both in papillary carcinoma (p=.001) and peritumoral lymphoid cells in the thyroid (p<.001). In addition, the proportion of PD-L1 expression in PTC cells was closely related to metastatic LNs (p=.036). Conclusions PD-L1 is a valuable predictive marker for LN metastasis in PTC. Immunomodulating therapies that inhibit PD-L1 might be an option for patients with LN metastasis.